Prostaglandin E2 potentiates interferon‐γ‐induced nitric oxide production in cultured rat microglia. Issue 4 (2nd February 2017) - Nagano, Takayuki; Nishiyama, Ryo; Sanada, Ayaka; Mutaguchi, Yukiko; Ioku, Anna; Umeki, Hirohisa; Kishimoto, Satoshi; Yamanaka, Daisuke; Kimura, Shinya H.; Takemura, Motohiko
Abstract : This study proposes prostaglandin E2 (PGE2 ) inflammatory action in microglia. Interferon‐γ (IFN‐γ) promoted signal transducer and activator of transcription 1 (STAT1) phosphorylation, followed by inducible nitric oxide synthase expression to produce nitric oxide (NO) detected as nitrite. IFN‐γ‐induced NO production was potentiated by PGE2 . PGE2 activated the prostanoid EP2 receptor to increase cyclic AMP (cAMP), but did not affect STAT1 phosphorylation. Thus, the potentiating effect of PGE2 on NO production is mediated by the EP2 receptor in microglia. Abstract: Prostaglandin E2 (PGE2 ) plays crucial roles in managing microglial activation through the prostanoid EP2 receptor, a PGE2 receptor subtype. In this study, we report that PGE2 enhances interferon‐γ (IFN‐γ)‐induced nitric oxide production in microglia. IFN‐γ increased the release of nitrite, a metabolite of nitric oxide, which was augmented by PGE2, although PGE2 by itself slightly affects nitrite release. The potentiating effect of PGE2 was positively associated with increased expression of inducible nitric oxide synthase. In contrast to nitrite release induced by IFN‐γ, lipopolysaccharide‐induced nitrite release was not affected by PGE2 . An EP2 agonist, ONO‐AE1‐259‐01 also augmented IFN‐γ‐induced nitrite release, while an EP1 agonist, ONO‐DI‐004, an EP3 agonist, ONO‐AE‐248, or an EP4 agonist, ONO‐AE1‐329, did not. In addition, the potentiating effect of PGE2 was inhibited by an EP2 antagonist, PF‐04418948, but not by an EP1 antagonist, ONO‐8713, an EP3 antagonist, ONO‐AE3‐240, or an EP4 antagonist, ONO‐AE3‐208, at 10 −6  M. Among the EP agonists, ONO‐AE1‐259‐01 alone was able to accumulate cyclic adenosine monophosphate (AMP), and among the EP antagonists, PF‐04418948 was the only one able to inhibit PGE2 ‐increased intracellular cyclic AMP accumulation. On the other hand, IFN‐γ promoted phosphorylation of signal transducer and activator of transcription 1, which was not affected by PGE2 . Furthermore, other prostanoid receptor agonists, PGD2, PGF2α, iloprost, and U‐46119, slightly affected IFN‐γ‐induced nitrite release. These results indicate that PGE2 potentiates IFN‐γ‐induced nitric oxide production in microglia through the EP2 receptor, which may shed light on one of the pro‐inflammatory aspects of PGE2 .